Implementasi Metode Supply Chain Management pada Sistem Informasi Manajemen UMSU (Universitas Muhammadiyah Sumatera Utara) Press Bebasis Web - Nugraha, Satria Harum; Suendri, Suendri (Program Studi Teknik Informatika Universitas Pamulang, 2024)
This study aims to improve management and distribution effectiveness at UMSU (Universitas Muhammadiyah Sumatera Utara) Press. UMSU Press is an institution that manages publishing and printing books by utilizing the creativity of the UMSU academic community as a skilled workforce. The main problem in the book publishing process is delays in book publication caused by miss communication between the client and the management of UMSU Press or the printer and the management of UMSU Press. The absence of a repository that functions as an archive makes UMSU Press not have a good track record due to a lack of attention to archive management, this is a secondary problem for UMSU Press to improve the reputation of UMSU Press. Clients who do not know the development process of book publishing and always ask about publishing developments are the final problem for UMSU Press. Supply Chain Management (SCM) is a method that integrates raw materials, production processes, and distribution processes by adjusting cost and time requirements. Laravel Framework is a website framework based on the PHP programming language with the concept of Model View Controller (MVC) which simplifies the process of developing information systems. To achieve good distribution and management flows, a system is needed that can help manage and monitor the development process of book publishing. By building a management information system using the Supply Chain Management (SCM) method using the Laravel framework, it can help reduce miss-communications that occur and increase the effectiveness of UMSU Press's performance, as well as help monitor the book publishing process so that clients can find out the progress of book publishing carried out by UMSU Press.